Electrophysiological findings in immune checkpoint inhibitor-related peripheral neuropathy - Chen, Xi (Clin Neurophysiol, 2019)
OBJECTIVE: To report the electrodiagnostic features of immune checkpoint inhibitor (ICI)-related neuropathy. METHODS: We retrospectively reviewed clinical presentations and electrodiagnostic features of 23 patients studied after receiving immune checkpoint inhibitors (ICIs). The presentations for electrodiagnostic evaluation included an acute neuropathy or neuromuscular junction disorder. We applied established electrodiagnostic criteria for polyneuropathy and acute demyelinating neuropathy. RESULTS: We identified acute demyelinating neuropathy (13 cases), axonal sensory motor neuropathy (5), pure sensory neuropathy (4) and mononeuropathy (1). 13 patients had acute demyelinating neuropathy confirmed by demonstrating demyelination in 2 or more nerves; 3 additional patients had demyelination in only one nerve. Analysis of motor nerve conduction parameters revealed demyelination involving median and ulnar nerve distal motor latencies as well as median, ulnar and peroneal nerve conduction velocities. Conduction block was found in median, ulnar and peroneal nerves. The remaining one-third patients without demyelination had acute painful axonal neuropathy. Coexisting myopathic changes (6) and neuromuscular junction dysfunction (4) were also identified. CONCLUSIONS: Our findings suggest that, while immune-mediated motor nerve demyelination is the primary underlying mechanism of ICI-related neuropathy, axonal painful neuropathy can also be an important presentation. Early recognition and effective intervention may reduce morbidity and permanent disability. SIGNIFICANCE: Electrophysiological studies might be useful in the evaluation of ICI-related neuropathy.